Photosynthetic behavior, growth and essential oil production of Melissa officinalis L. cultivated under colored shade nets - Oliveira, Graziele C.; Vieira, Willyam L.; Bertolli, Suzana C. [UNESP]; Pacheco, Ana Claudia (Inst Investigaciones Agropecuarias, 2016)
The modulation of light is of importance during cultivation of medicinal plants to obtain desirable morphological and physiological changes associated with the maximum production of active principles. This study aimed to evaluate the effect of the light spectrum transmitted by colored shade nets on growth, essential oil production and photosynthetic behavior in plants of lemon balm (Melissa officinalis L.) Plants were cultivated in pots for 4-mo under black, red, and blue nets with 50% shading, and full sunlight exposure. Biometric and anatomical variables, essential oil yield, global solar radiation, photon flux density, chlorophyll content, and gas exchange parameters were measured in M. officinalis leaves. The results showed that despite being considered a partial shade plant, this species is able to adapt to full sunlight conditions without increasing biomass production. The spectral changes provided by colored shade nets did not caused any noticeable change in leaf anatomy of M. officinalis. However, the use of blue net resulted in increments of 116% in plant height, 168% in leaf area, 42% in chlorophyll content and 30% in yield of essential oil in lemon balm plants. These plant's qualities make the use of blue net a cultivation practice suitable for commercial use.
Keywords: Medicinal plant; development; gas exchange; leaf anatomy